PENERAPAN TEKNOLOGI TEPAT GUNA PENGOLAHAN BIODIESEL PADA KELOMPOK USAHA BANUA BERSAMA ENERGY – KABUPATEN TANAH LAUT - nugraheni, ika; Artika, Kurnia Dwi; Suasri, Eni (Jurnal Pengabdian Kepada Masyarakat (MEDITEG), 2022)
Tanah Laut Regency is a huge area with a large population to generate a lot of household/kitchen waste. Furthermore, Tanah Laut has a relatively significant waste of spent cooking oil due to its huge number of restaurants and food processing enterprises. The Banua Bersama Energy is a company that collects leftover cooking oil and sells it outside of the region. So far, sales have been made in the form of wasted cooking oil that has not been processed. This partner group does not yet have the knowledge and technology as them when it comes to processing spent cooking oil. It is envisaged that through this PKM program, partner groups can increase the economic worth and advantages of wasted cooking oil that has been collected. With the socialization to Biodiesel users, it has helped partners in fulfilling the market share from the production of processed used cooking oil.